Maternal and Perinatal Outcomes in Women with Insulin Resistance - Temming, Lorene A.; Tuuli, Methodius G.; Stout, Molly J.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2016)
Objective This study aims to estimate the risks of adverse maternal and perinatal outcomes in women with insulin resistance below the threshold of gestational diabetes mellitus (GDM).Methods This was a retrospective cohort study of 5,983 women with singleton pregnancies undergoing universal GDM screening between 24 and 28 weeks gestation. Subjects were divided into those with a normal 1-hour glucose challenge test (GCT), those with an elevated GCT with all normal values on a 3-hour glucose tolerance test (GTT), and those with an elevated GCT with one abnormal value on GTT. Outcomes included macrosomia, pregnancy-induced hypertension (PIH), cesarean section and operative delivery, shoulder dystocia, indicated-preterm birth, and other neonatal outcomes. Logistic regression was performed to compare outcomes among groups.Results The risk of macrosomia was increased for those with an elevated GCT and all normal values on GTT (adjusted odds ratio [aOR], 1.71; 95% confidence interval [CI]: 1.12, 1.97), and for those with an elevated GCT and one abnormal value (aOR, 2.69; 95% CI: 1.49, 4.83). Risks of PIH, cesarean section, and indicated-preterm birth were also increased in those with an elevated 1-hour GCT and no GDM.Conclusion There are increased risks of macrosomia, PIH, indicated-preterm birth, and cesarean section among those with insulin resistance even in the absence of GDM.
Keywords: insulin resistance; elevated 1-hour glucose challenge test; gestational diabetes mellitus; macrosomia